The Bingah Scale: A Development of the Happiness Measurement Scale in the Sundanese - Tasya Augustiya; Ayu Lestari; Heru Budiman; Raissa Maharani; Mita Anggraini (Jurnal Psikologi Islam dan Budaya, 2020)
This study was conducted to create an instrument that measures the conditions of happiness felt by the Sundanese in Indonesia. This scale is named the Bingah Scale. The measurement instrument modification approach was used in this study, where the researcher had chosen the theoretical construct that was relevant to the happiness construct in the Sundanese, then made new items that measured the construct. This modification was carried out to get a more comprehensive measuring instrument because it was adjusted to the language and culture where the measuring instrument was used. The number of respondents involved in the study amounted to 526 participants who were the representations of the Sundanese who were selected using a purposive sampling technique. The results showed that there were 21 items, both psychometrically and feasible to be used as appropriate instruments to measure the condition of happiness in Sundanese.